PENGARUH PENGGUNAAN ALAT PERAGA DAKON BILANGAN TERHADAP HASIL BELAJAR KOGNITIF MATEMATIKA PESERTA DIDIK - Jaslina, Nurin; Tampubolon, Budiman; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to provide the impact of using the dakon number instrument on students' cognitive outcomes in mathematics learningl in lclass Vl of lSD Negeril 11l East lPontianak. The lmethod applied is an experiment withl la Quasi lExperimental ldesign, namely lNonequivalent Control Groupl Design. The total sample consisted of 48 students from two classes. The research population included 24 studentsl from lclass VAl and 24 lstudents lfrom classl VB. Data collection was carried out through measurement techniques, using written tests in presentation format as a data collection tool. From data analysis, the average final test result for the experimental class was 74.3, while for the control class it was 63.625. Hypothesis testing with the t test (separated variance) produces a t value of 1.908, while t table (Î± = 5% and dk = 24 + 24 "“ 2 = 46) is 1.6801. With tcount ttable, Ha is accepted. These results indicate that therel is la lsignificant differencel in lthe final ltest resultsl between the two classes of studentsl in thel experimental classl and thel control lclass, in other words, it proves thatl therel is an influencel of lthe usel of number dakon teachingl aids onl thel cognitive mathematics learning outcomes of class V students at SD lNegeri 11 East Pontianak. Basedl on lthe resultsl of lthe effect size calculation, the result was 1.119, which is included in the high criteria